Dialectics of perisomatic inhibition—The unity and conflict of opposites - Rozov, Andrei; Jappy, David John; Maltseva, Ksenia; Vazetdinova, Alina; Valiullina-Rakhmatullina, Fliza (Frontiers in Neural Circuits, 2024)
Over the past three decades, a great deal of attention has been paid to the study of perisomatic inhibition and perisomatic inhibitory basket cells. A growing body of experimental evidence points to the leading role of perisomatic inhibitory cells in the generation of oscillatory activity in various frequency ranges. Recently the link between the activity of basket cells and complex behavior has been demonstrated in several laboratories. However, all this is true only for one type of perisomatic inhibitory interneuron—parvalbumin-positive basket cells. Nevertheless, where parvalbumin-positive basket cells are found, there is another type of basket cell, cholecystokinin-positive interneurons. These two types of interneurons share a number of common features: they innervate the same compartments of target neurons and they often receive excitation from the same sources, but they also differ from each other in the synchrony of their GABA release and expression of receptors. The functional role of cholecystokinin-positive basket cells in oscillatory activity is not so obvious. They were thought to be involved in theta oscillations, however recent measurements in free moving animals have put some doubts on this hypothesis. Therefore, an important question is, whether these two types of basket cells work synergistically or perform opposing actions in functional networks? In this mini-review, we attempt to answer this question by putting forward the idea that these two types of basket cells are functionally united as two entities of the same network, and their opposing actions are necessary to maintain rhythmogenesis in a “healthy”, physiological range.